Control of Costs and Working Time of Road Improvement Kh. Syafi'i - Suci Fitriyani (Neutron, 2022)
This study aims to analyze the optimum time and cost of completing the work after the acceleration of the duration of the KH Road Improvement Project. Syafi'i in Suci Village, Manyar District, Gresik Regency using the Microsfot Project. Acceleration analysis by adding working hours and considering the resulting critical path. This research is also to find out the project performance compared to the initial project plan in terms of cost and time, to find out the estimated final cost of the project needed after the acceleration of implementation.